KARAKTERISTIK KIMIA DAN SENSORI NATA DE COCOA DARI KULIT BUAH DAN PULPA COKLAT (Theobroma cocoa L) - Zulfa, Fitriyah; Rismayanti, Fitriya Devi (Jurnal Teknologi Hasil Pertanian, 2017)
The area of cocoa plantations in East Java reaches 50 thousand hectares and in Madiun reaches 4,180 Ha, with annual production reaching 406 tons on average. Cocoa production which produces a lot of agroindustrial waste in the form of fruit peel and cocoa pulp that needs to be utilized. The pulp and cocoa peel contain sugar, minerals and fiber which can be used to make nata de cocoa. This study aims to determine the chemical characteristics (carbohydrate and fiber content) and sensory analysis (color, texture, taste and overall) of nata de cocoa from the peel of cocoa and pulp. The ingredients needed are pulp, scraped cocoa peel, sugar, nitrogen sources, vinegar and acetobacter xyllinium. Tools needed for scrapers, blenders, filters (mori cloth), spatulas, scales, measuring cups, basins, boiling pans, wood stirrers, stoves, knives, snacks, fermentation containers, sterile newspapers, rubber, pH meters, thermometers. The tools used for carbohydrate and fiber testing (Luff Schrol and strong acid hydrolysis of strong bases) are reflux, hot plate, burette, clamp, stative, Erlenmeyer, glasa breaker, stirring rod, volume pipette, suction ball, drop pipette, measuring flask , glass funnel. Chemical analysis of carbohydrate content of nata de cocoa is 10.98% and fiber content reaches 13.00%. Sensory analysis of nata de cocoa including color obtained a score of 4.85 (like), 4.7 (like), flavor 4.1 (rather like). Overall appearance (overall) obtained an average score of 4.55, which means that the nata de cocoa produced by this study is preferred.